Students’ Perception of Using Microsoft Teams in English Online Learning at SMAN 10 Pinrang - Suciati Faisal; Asfah Rahman; Munir Munir (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
This study aims to explore students' perception of Using Microsoft teams in English Online Learning. The present study applies descriptive qualitative method to achieve the research objectives, the data collected were in the form of questionnaire and interviews. The subject of this study was students of SMAN 10 Pinrang class XII IPA 3 academic 2021/2022. The sample of the questionnaire were 29 students, and the interview were 5 students who were taken using simple cluster random sampling technique. Based on the results of the study, researchers found that students' perception of the use of Microsoft teams in English online learning as a flexible, affective, effective and facilitate interaction between teachers and students continues to run smoothly during online learning. Of the 29 students who filled out the questionnaire, 22 students agreed that online learning using Microsoft teams is more effective because it comes with a variety of complete features that can make it easier for students to learn online during a pandemic.